Gene Co-expression Analysis Identifies Histone Deacetylase 5 and 9 Expression in Midbrain Dopamine Neurons and as Regulators of Neurite Growth via Bone Morphogenetic Protein Signaling - Mazzocchi, Martina; Wyatt, Sean L.; Mercatelli, Daniela; Morari, Michele; Morales-Prieto, Noelia; Collins, Louise M.; Sullivan, Aideen M.; O’Keeffe, Gerard W. (Frontiers in Cell and Developmental Biology, 2019)
Parkinson’s disease is characterised by the intracellular accumulation of -synuclein which has been linked to early dopaminergic axonal degeneration. Identifying druggable targets that can promote axonal growth in cells overexpressing -synuclein is important in order to develop strategies for early intervention. Class-IIa histone deacetylases (HDACs) have previously emerged as druggable targets, however it is not known which specific class-IIa HDACs should be targeted to promote neurite growth in dopaminergic neurons. To provide insight into this, we used gene co-expression analysis to identify which, if any, of the class-IIa HDACs had a positive correlation with markers of dopaminergic neurons in the human substantia nigra. This revealed that two histone deacetylases, HDAC5 and HDAC9, are co-expressed with TH, GIRK2 and ALDH1A1 in the human SN. We further found that HDAC5 and HDAC9 are expressed in dopaminergic neurons in the adult mouse substantia nigra. We show that siRNAs targeting HDAC5 or HDAC9 can promote neurite growth in SH-SY5Y cells, and that their pharmacological inhibition, using the drug MC1568, promoted neurite growth in cultured rat dopaminergic neurons. Moreover, MC1568 treatment upregulated the expression of the neurotrophic factor, BMP2, and its downstream transcription factor, SMAD1. In addition, MC1568 or siRNAs targeting HDAC5 or HDAC9 led to an increase in Smad-dependent GFP expression in a reporter assay. Furthermore, MC1568 treatment of cultured rat dopaminergic neurons increased cellular levels of phosphorylated Smad1, which was prevented by the BMP receptor inhibitor, dorsomorphin. Dorsomorphin treatment prevented the neurite growth-promoting effects of siRNAs targeting HDAC5, as did overexpression of dominant-negative Smad4 or of the inhibitory Smad7, demonstrating a functional link to BMP signalling. Supplementation with BMP2 prevented the neurite growth-inhibitory effects of nuclear-restricted HDAC5. Finally, we report that siRNAs targeting HDAC5 or HDAC9 promoted neurite growth in cells overexpressing wild-type or A53T--synuclein and that MC1568 protected cultured rat dopaminergic neurons against the neurotoxin, MPP+. These findings establish HDAC5 and HDAC9 as novel regulators of BMP-Smad signalling, that additionally may be therapeutic targets worthy of further exploration in iPSC-derived human DA neurons and in vivo models of Parkinson’s disease.